2022
DOI: 10.3390/nu15010076
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Non-Communicable Disease Biomarkers: A Network Meta-Analysis and Nutritional Geometry Approach

Abstract: Quantitative rankings of multiple dietary patterns for their effects on non-communicable disease (NCD) biomarkers is lacking and would inform primary prevention strategies. Accordingly, a network meta-analysis (NMA) was conducted to compare and rank the effects of different dietary patterns on NCD biomarkers, and associations of dietary patterns’ underlying macronutrient composition with NCD biomarkers were determined by a nutritional geometry approach. Randomised controlled trials (RCTs) were eligible for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…These results were in line with other two descriptive reviews, the first including 2,890 overweight/obese adults [ 19 ], the second 8,969 vegetarian children aged 0–18 years [ 20 ]. Furthermore, a meta-analysis by Liang et al described significantly lower TC (from -0.36 to -0.24 mmol/L) in people adopting plant based diets vs. people adopting western habitual diets [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results were in line with other two descriptive reviews, the first including 2,890 overweight/obese adults [ 19 ], the second 8,969 vegetarian children aged 0–18 years [ 20 ]. Furthermore, a meta-analysis by Liang et al described significantly lower TC (from -0.36 to -0.24 mmol/L) in people adopting plant based diets vs. people adopting western habitual diets [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight reviews focused on the effects of vegetarian diet on serum high-density lipoprotein cholesterol (HDL-C) levels. Six [ 15 , 17 , 18 , 21 23 ] found no significant difference between vegetarians and omnivores, when considering normal weight and overweight/obese people. On the contrary, the study by Dinu et al [ 14 ], based on 51 studies, for a total of 6,194 vegetarian adults, reported a WMD −0.15 mmol/L (95%CI: −0.19, −0.11).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations